The cellular transducer in damage-stimulated bone remodelling - Hazenberg, Jan Geert (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2004)
People with osteoporosis, osteopenia or weight baring joint replacement, due to an altered loading configuration, are more susceptible to microdamage accumulation than normal human beings as are athletes who undertake strenuous exercise. Experimental evidence has linked bone adaptation to microdamage, and to increased cell activity. In this work, a theoretical investigation, using fracture mechanics, was used to assess which mechanisms might be present in bone to detect microcracks and to initiate an adequate response to prevent total fracture of bone. Two mechanisms were investigated; I) detection by rupturing of the cellular material itself and, II) strain detection by the osteocytes. Rupturing of cell processes due to crack opening and shear displacements was found to provide a feasible mechanism by which bone can detect and estimate the size of a microcrack. Analytical and numerical methods were developed to predict these crack face displacements and validated experimentally. Failure criteria were set based on the dimensions of an individual cell or cell process. Using these criteria, it was predicted that cracks slightly longer than those normally found in bone under normal physiological loads would cause ruptured cell processes. Smaller cracks, even under severe loading conditions would not be capable of doing so. For cracks which were several times longer than the typical length, even a moderate loading level would result in ruptured cell processes. Experimental work carried out using cell staining confirmed that crack displacements are capable of tearing cell processes. Rupturing of osteocytes near the crack tip was predicted to be very unlikely since strain levels are less than the fatigue failure strain of the material.
Keywords: Mechanical Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin